Avapritinib in the treatment of systemic mastocytosis with associated acute myeloid leukemia after poor graft function following allogeneic hematopoietic stem cell transplantation: a case study and review of the literature - Mi, Ruihua; Li, Xiang; Chen, Lin; Wang, Lin; Ma, Yixuan; Fu, Yuewen; Wei, Xudong (Frontiers in Oncology, 2025)
IntroductionThis case is reported due to its novelty in demonstrating the efficacy of avapritinib, a selective KIT inhibitor, in a rare systemic mastocytosis-associated acute myeloid leukemia (SM-AML) patient with non-D816V KIT mutations and RUNX1::RUNX1T1 fusion. Avapritinib is established for KIT D816V-mutant advanced systemic mastocytosis (AdvSM). However, its role in non-D816V KIT mutant SM-AHN post-allogeneic hematopoietic stem cell transplantation (Allo-HSCT) remains unexplored, highlighting the need to document this therapeutic challenge and outcome.Case presentationA 15-year-old Asian male with SM-AML underwent induction chemotherapy, targeted therapy, and Allo-HSCT, but experienced graft failure with persistent mastocytosis. Post-Allo-HSCT avapritinib was initiated due to high proportion of mast cells (MCs). After 14 months, the patient achieved minimal residual disease (MRD)-negative complete remission, full donor chimerism (100%), and sustained hematologic recovery without adverse events. MC burden declined from 14.06% to 0.3%, and RUNX1::RUNX1T1 fusion became undetectable.ConclusionThis case highlights avapritinib’s potential as a salvage therapy for non-D816V KIT mutant SM-AML post-Allo-HSCT, effectively reducing MC clones and restoring donor chimerism. It suggests that avapritinib may bridge therapeutic gaps for atypical KIT-mutant systemic mastocytosis with associated hematologic neoplasm (SM-AHN) that is ineligible for Allo-HSCT or relapsed. Prospective trials are warranted to validate its efficacy, optimize dosing, and explore synergies with Allo-HSCT, offering new strategies for these high-risk patients.